2021
DOI: 10.1177/08853282211060544
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and in vitro release kinetics of doxorubicin-loaded magnetosomes

Abstract: The doxorubicin (DOX) was successfully coupled to the magnetosomes from Acidithiobacillus ferrooxidans ( At. ferrooxidans) by genipin bridging. The parameters (magnetosome concentration, DOX concentration, genipin concentration-, and cross-link time) expected for temperature significantly influenced the coupling rate. Bacterial magnetosome-doxorubicin complexes (BMDCs) were characterized by transmission electron microscope (TEM), particle size analyzer and Fourier transform infrared spectroscopy. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…31 It has been reported that magnetosomes can be synthesized by MTB such as Magnetospirillum magnetotacticum , Magnetospirillum gryphiswaldense and Magnetospirillum magneticum , and non-MTB such as A. ferrooxidans , Ferroplasma thermophilum and Leptospirillum ferrooxidans . 21 In this work, non-MTB A. ferrooxidans BYM was employed to produce magnetosomes in airlift bioreactor. Results showed the magnetosome yield of A. ferrooxidans BYM is of the same order of magnitude or lower than that reported for MTB (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…31 It has been reported that magnetosomes can be synthesized by MTB such as Magnetospirillum magnetotacticum , Magnetospirillum gryphiswaldense and Magnetospirillum magneticum , and non-MTB such as A. ferrooxidans , Ferroplasma thermophilum and Leptospirillum ferrooxidans . 21 In this work, non-MTB A. ferrooxidans BYM was employed to produce magnetosomes in airlift bioreactor. Results showed the magnetosome yield of A. ferrooxidans BYM is of the same order of magnitude or lower than that reported for MTB (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…29 In the contrary, A. ferrooxidans BYM can grow in the low-cost medium and non-fastidious culture conditions, which is favored for industrial production of magnetosomes. 21,32…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations